Aggregate effects of a universal social insurance fiscal reform - Arturo Antón; Julio Leal (Banco de México, 2015)
In a typical developing country, coverage of the contributory social security system is low. We analyze the aggregate effects of a revenue-neutral fiscal-cum-social policy reform that consists of: 1) the implementation of universal social insurance to replace the system with low coverage; and 2) the elimination of the social security payroll tax to replace it with a generalized VAT. We find that this reform increases productivity by 2 percent and output by 3 percent as it improves the allocation of resources across firms and sectors, and generates a substantial change in occupational choices. Thus, wages (before transfers) increase for all employees. Also, due to the reconfiguration of transfers, earnings (wages after transfers) for informal employees increase relative to the earnings of formal employees, which decreases inequality. However, the reform could affect some groups in the population,given the regressive nature of VAT and heterogeneity in the valuation of transfers across workers.
Keywords: E62; H55; O17; O47; 330; Universal Social Insurance; Fiscal Reform; Inequality; VAT; Allocation of Resources across Firms and Sectors